ANALISIS TINGKAT KEMISKINAN DI PROVINSI JAWA BARAT, 2008-2012 - , Lia Rosmalia, Prof. Dr. Nopirin, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to analyze the inequality of poverty between regency/city in West Java Province, to analyze the factors that affect the level of poverty and analyze spatial patterns of poverty in the province of West Java. The analysis tool is used to analyze the Theil entropy index of inequality, using panel data regression Random Effect as the best model to analyze the influence and Geographic Information Systems (GIS) for spatial analysis. The data used are secondary data all regency/city in West Java province as much as 130 units of observation. The results showed that the inequality of poverty in the province of West Java continue to decline shown by Theil entropy index continued to decline in 2008 and 2012 amounted to 0,2224 at 0,0947. The increase in GDP per capita and government spending and significant negative effect of the poverty rate in the province of West Java. The increase in GDP per capita in the province of West Java will reduce poverty through increased per capita consumption, while government spending will reduce poverty through infrastructure spending allocations education, health and infrastructure facilities such as markets, roads, etc. Other variables that increased levels of open unemployment effect is not significant to raise the level of poverty in the province of West Java. Based on the analysis of spatial region with the category of very low levels of poverty, low and medium, have a tendency to increase in GDP per capita, government spending and the trend of declining unemployment rate. While areas with high poverty levels and categories are very high, has tended to the unequal distribution of income in the lower classes of society. The unemployment rate has now fallen but is accompanied by increased allocation of workers is not full and not well targeted government spending on poverty reduction.